A GIS-based relational data model for multi-dimensional representation of river hydrodynamics and morphodynamics. (March 2015) - Kim, Dongsu; Muste, Marian; Merwade, Venkatesh
Abstract: The emerging capabilities of the geo-based information systems to integrate spatial and temporal attributes of in-situ measurements is a long-waited solution to efficiently organize, visualize, and analyze the vast amount of data produced by the new generations of river instruments. This paper describes the construct of a river data model linked to a relational database that can be populated with both measured and simulated river data to facilitate descriptions of river features and processes using hydraulic/hydrologic terminology. The proposed model, labeled Arc River, is built in close connection with the existing Arc Hydro data model developed for water-related features to ensure the connection of the river characteristics with their floodplains and watersheds. This paper illustrates Arc River data model capabilities in conjunction with Acoustic Doppler Current Profiler measurements to demonstrate that essential river morphodynamics and hydrodynamics aspects can be described using data on the flow and its boundaries. Highlights: Represent river data in a curvilinear coordinate system to support river channel oriented spatial analyses. Represent multidimensional river features through points, lines, polygons, and volumes. Represent simulated gridded data for river channels that can be readily coupled with observed data. Represent spatio-temporal evolution of dynamic river objects using Eulerian or Lagrangian observational frameworks. Efficiently store and retrieve data acquired in-situ along with the ancillary metadata.